Clinical analysis of reversible splenial lesion syndrome in Chinese adults: A retrospective study of 11 cases. Issue 36 (4th September 2020) - Gao, Xiaoyu; Feng, Qiaochan; Arif, Saeed; Liaqat, Jahanzeb; Li, Bing; Jiang, Kun
Abstract : Abstract: Reversible splenial lesion syndrome (RESLES) is a clinico-radiological entity that defines a reversible lesion in the splenium of the corpus callosum (SCC) on magnetic resonance imaging (MRI). The clinical and radiological characteristics of RESLES are poorly defined and most RESLES literature is in the form of case reports. We reviewed the clinical and radiological data from 11 RESLES patients in order to more clearly describe the characteristics of this disorder in adults. Patients included in this study were diagnosed with RESLES from May 2012 to March 2018. We collected clinical, imaging, and laboratory data of 11 adult patients from Neurology Department of the Affliated Yantai Yuhuangding Hospital of Qingdao University. After analyzing various clinico-radiological features and laboratory parameters, including serum sodium, pathogen testing, cerebrospinal fluid (CSF) studies, electroencephalography (EEG), and MRI findings, we made a diagnosis of RESLES based on the criteria proposed previously by Garcia-Monco et al. Of the 11 patients, 7 (63.63%) were male and 4 (36.36%) were female, ranging in age from 24 to 62 years with an average age of 31.48 ± 11.47 years. Seven cases occurred in the months of winter and spring (December–March). The primary clinical symptoms were headache, seizure, disturbance of consciousness, mental abnormality, and dizziness. All 11 patients had lesions in the SCC and all the lesions disappeared or significantly improved on follow-up imaging that was done within a month of symptom resolution. We found 5 (45.45%) patients had a CSF opening pressure >180 mmH2 O, in addition to elevated protein and(or) leukocytes levels in 3 (27.27%) patients. The serum sodium concentration in 6 (54.55%) patients was low (<137 mmol/L) and EEG showed nonspecific slowing in waves 4 (36.36%) patients. When we encounter clinical manifestations such as headache accompanied with mental symptoms, disturbance of consciousness or epilepsy, and brain MRI finds lesions of the corpus callosum, we should consider whether it is RESLES. In order to find out the possible cause of the disease, we should carefully inquire about the history of the disease, complete etiology examination, and CSF tests. Of course, it is one of the necessary conditions for the diagnosis that the lesions in the corpus callosum are obviously relieved or disappeared.